(untitled) (Dentika: Dental Journal, 2014)
Brushing teeth with suitable toothpaste is the most effective way to remove plaque and prevent accumulation of plaque to prevent gingivitis. This research aims to examine the effectivity of toothpaste contained Dipotassium Glycyrrhizinate 0.05% and IPMP 0.05% as active ingredients toward gingival health. Double-blind randomized parallel group clinical trial was conducted. The amount of samples were 30 persons randomly assigned to used tested toothpaste, and 30 other persons use placebo. Measurement of Salivary Occult Blood Test (SOBT), Bleeding on Probing (BOP) and Gingival Index (GP) were performed before and after 3 months of toothpaste use. The results showed that after 3 months there were significant decrease (p< 0.05) in all values of SOBT (26 into 8), BOP (15.2 into 3.4), GI (0.5 into 0.1). In conclusion, the tested toothpaste provided protection against gingivitis (gum protection) 2 times better and a significant difference compared to placebo toothpaste